2018
DOI: 10.1021/acs.nanolett.8b03510
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Structural Ultrabattery Composite

Abstract: Here we demonstrate a composite material exhibiting dual multifunctional properties of a structural material and a redox-active battery. This incorporates three-dimensional aligned carbon nanotube interfaces that weave together a structural frame, redox-active battery materials, and a Kevlarinfiltrated solid electrolyte that facilitates ion transfer. Relative to the total measured composite material mass, we demonstrate energy density up to ∼1.4 Wh/kg, elastic modulus of 7 GPa, and tensile strength exceeding 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“…Furthermore, almost all of these demonstrate poor multifunctional performance, where either the electrical or the mechanical performance is prioritized. For example, Thakur and Dong [ 27 ] reported an energy density of 24 Wh kg −1 at an elastic modulus of only 0.29 GPa, whereas Meng et al [ 28 ] demonstrated a structural battery material with an elastic modulus of 7.0 GPa but a low energy‐storage capability of 1.4 Wh kg −1 . Moyer et al reported a multifunctional device, exploiting CFs as collectors.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, almost all of these demonstrate poor multifunctional performance, where either the electrical or the mechanical performance is prioritized. For example, Thakur and Dong [ 27 ] reported an energy density of 24 Wh kg −1 at an elastic modulus of only 0.29 GPa, whereas Meng et al [ 28 ] demonstrated a structural battery material with an elastic modulus of 7.0 GPa but a low energy‐storage capability of 1.4 Wh kg −1 . Moyer et al reported a multifunctional device, exploiting CFs as collectors.…”
Section: Resultsmentioning
confidence: 99%
“…Structural energy and power is an emerging field that combines the mechanical properties of structural composites with the energy-storage properties of batteries and supercapacitors. 1,2 Recent interest in structural energy and power is driven by the potential for reduced mass and volume, which promises lighter vehicles and aircraft, more miles between recharging, and enhanced safety. 3,4 However, battery and supercapacitor electrodes do not possess good mechanical properties as they are often formed from brittle materials; 5 this leads to unacceptably low values in the multifunctional efficiency parameter (<1), which is the performance metric used to describe the combined mechanical and energy-storage properties.…”
Section: Introductionmentioning
confidence: 99%
“…27 These values were comparable to those measured for carbon fiber based structural batteries fabricated by conventional lay-up processes. 8,23,6669 Combined with the flexibility in preparing complex geometry composite parts, it well demonstrated the potentials of the proposed 3D printing technique in fabricating structural battery composites with carbon fibers. With each SPE-coated carbon fiber dispersed in the cathode doped matrix and working as a micro-battery cell, the corresponding dramatic intercalation surface area between electrolyte and active materials 6,45 can potentially help the 3D structural battery composite achieve higher energy density and specific capacities with further improvement of the 3D printing process.…”
Section: Resultsmentioning
confidence: 78%